Serbia since 1989 : politics and society under Milos̆ević and after - Ramet, Sabrina P., 1949-; Pavlaković, Vjeran (Jackson School publications in international studies., 2007)
During thirteen years in power, Slobodan Milosevic and his cohorts plunged Yugoslavia into wars of ethnic cleansing, leading to the murder of thousands of civilians. Their regime also subverted the nation's culture, twisted the political main-stream into a virulent nationalist mold, sapped the economy through war and the criminalization of the free market, returned to gender relations of a bygone era, and left the state so dysfunctional that its peripheries - Kosovo, Vojvodina, and Montenegro - have been struggling to maximize their distance from Belgrade. The essays in this book reveal a Serbia that is still traumatized from Milosevic's rule and groping toward redefining its place in the world.